Holistic Diagnosis and Comprehensive Management of a 30-Year-Old Pregnant Woman (Mrs. N) with High-Risk Pregnancy due to Chronic Energy Deficiency and Anemia at Bangetayu Community Health Center, Semarang - Fatuh Rohman; Ratnawati; Aris Maulana (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
ABSTRACT Background: High-risk pregnancy conditions, such as chronic energy deficiency (CED) and anemia, are significant public health concerns impacting both maternal and fetal outcomes. Purpose(s): This research aims to conduct a more in-depth study on the case of chronic energy deficiency (CED) and anemia in patient Ms. N at Sembungharjo Village, Bangetayu Health Center, Semarang. Methods: This case study examines a 30-year-old woman (Mrs. N) with a 28-week pregnancy complicated by CED (upper arm circumference 22.5 cm) and anemia (hemoglobin 10.1 g/dL) at Bangetayu Community Health Center, Semarang. A holistic diagnostic approach involving medical history, nutritional status, and family and environmental factors was carried out. Interventions included iron and folic acid supplementation, fortified food provision, and intensive health education—targeting both the patient and her family. Results: Results showed the patient’s knowledge and dietary practices were key contributors to persistent nutritional deficiencies. Functional family support and multidisciplinary collaboration between the health centre team, community cadres, and family members were emphasized for effective management. The study underlines the necessity of early nutritional and preventive interventions during pregnancy to mitigate risks of stunting and adverse neonatal outcomes. Conslusion: Comprehensive, community-oriented, and family-centered care is vital for improving health in high-risk pregnancies at the primary care level.